The differences in tuberculosis notifications and outcomes among males and females in Colombo, Sri Lanka - Chandima Hemachandra; Sudath Samaraweera; Arunasalam Pathmeswaran (College of Community Physicians of Sri Lanka, 2023)
Introduction: More males than females are reported with tuberculosis (TB). Assessment of disparities between the two groups would permit adopting targeted interventions. Objectives: To describe the differences in notification rates, sputum investigations and treatment outcomes of male and female TB patients Methods: A descriptive follow-up study was conducted among 2169 adult TB patients registered in the Colombo District Tuberculosis Register using registry data. Comparisons were made between males and females using Chi-squared test and risk ratio (RR). Results: Males had a higher TB notification rate (161 per 100 000) than females (79 per 100 000) and the highest notification rates were observed in 65-74-year-old age category in both groups. A higher proportion of males than females had pulmonary TB (78.2% in males and 59.7% in females; p<0.05). More males than females had a positive (RR=1.09; 95% CI: 1.05, 1.13) or high-grade sputum smear result (RR=1.15; 95% CI: 1.01, 1.31). Both groups had similar sputum conversion rates at the end of acute phase (80.4% vs. 84.1%). More males were lost to follow up compared to females (10.7% vs. 3.1%, p<0.05). Conclusions & Recommendations: The observed differences between males and females highlight the need to examine TB data disaggregated by sex and to have more sensitive diagnostics for females.